Etika Hiburan dalam Perspektif Hadis: Analisis terhadap Aplikasi TikTok - Husna, Arinal; Suparwany, Suparwany; Roslaili, Yuni (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2023)
The TikTok application is an entertainment medium that allows its users to do freestyle, such as dance, lip sync, challenges, etc., which was once banned in Indonesia because it contained negative content. This study discusses the ethics of entertainment from a hadith perspective, with the main focus being the TikTok application media. This qualitative research is library research with a descriptive analysis approach. The theory used is thematic hadith theory. The thematic hadith method is carried out by tracing the hadiths using the lafadz "لَهْوٌ" and "لَعِب" and is limited to only the hadiths contained in the Polaris sittah book, while the criticism of sanad and matan is only carried out on one path and not on all tracks. Primary data sources include the books al-Kutub al-Sittah, Mu'jam al-Mufahras, Tahzib al-Kamal, and Syarah Hadith, while secondary sources include books, articles, and scientific writings about TikTok and entertainment, as well as Software Hadith Lidwa Pusaka and Maktabah Syamilah. The results of the study show that when viewed from the hadiths of the Prophet Muhammad, entertainment is permissible as long as it is in accordance with the ethics of entertainment, such as not being excessive and negligent, not contrary to Islamic law, and not arousing lust. The TikTok application has many negative uses, such as dancing with nakedness and tabarruj, which can arouse lust, singing or lip syncing accompanied by neglectful music, and using sentences that are not educational, as well as the many types of content that can make a person addicted and inattentive. Therefore, the author considers that this application is irrelevant to the hadiths of the Prophet regarding entertainment.